2021
DOI: 10.1139/cjp-2020-0538
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, photoluminescence, and antibacterial activities of silica-graphene oxide composites

Abstract: In this research, a novel thin film Si-GO10 and nano-powders Si-GO30 of silica-graphene oxide composite were prepared via sol-gel method and deposited on glass substrates using spray pyrolysis. XRD results showed a relatively strong peak in graphite layer that corresponds to the plane of (002). TEM images displayed that SiO<sub>2</sub> nano-particles were randomly distributed on the surface of Si-GO30 sample, and the particle size in these nano-powders was below 50 nm. Moreover, silica nano-particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The results of the antimicrobial test of GO/SiO2 against Escherichia coli and Staphylococcus aureus with the disc diffusion method (Table 2 and Figure 6) showed that the inhibitory power of E. coli was stronger than S. aureus; The increase in GO-SiO2 (ppm) concentration further strengthens the antibacterial activity of the E. coli stable. Thus, the membrane material will be confirmed to have resistance to bacterial growth (E. coli and S. aureus) [36]. Bacterial-mediated infections can cause various acute or chronic diseases and antibiotic resistance in pathogenic bacteria has become a serious health problem.…”
Section: Anti-bacterial Of Go/sio2 Compositementioning
confidence: 99%
See 1 more Smart Citation
“…The results of the antimicrobial test of GO/SiO2 against Escherichia coli and Staphylococcus aureus with the disc diffusion method (Table 2 and Figure 6) showed that the inhibitory power of E. coli was stronger than S. aureus; The increase in GO-SiO2 (ppm) concentration further strengthens the antibacterial activity of the E. coli stable. Thus, the membrane material will be confirmed to have resistance to bacterial growth (E. coli and S. aureus) [36]. Bacterial-mediated infections can cause various acute or chronic diseases and antibiotic resistance in pathogenic bacteria has become a serious health problem.…”
Section: Anti-bacterial Of Go/sio2 Compositementioning
confidence: 99%
“…The use of GO material in membrane preparation will provide biosafety advantages [22]. Likewise, the presence of SiO2 nanoparticles, also has excellent properties as an anti-bacterial material [36,37].…”
Section: Anti-bacterial Of Go/sio2 Compositementioning
confidence: 99%